Complex gendered agency in Mexico: how women negotiate hierarchies of fear to search for the disappeared - Zulver, JM (Bristol University Press, 2023)
Fear and agency are complex, interrelated and gendered phenomena for the madres buscadoras, the women searching for the disappeared in Mexico. These women operate in a context of unrelenting, multisided violence. At the same time, they choose to engage in activism that puts them at heightened risk of violence at the nexus of criminal organisations, state corruption and insecurity. This article investigates how the madres navigate contexts of gendered violence in Veracruz, Mexico, to engage in expressions of complex gendered agency. It makes the argument that we can understand why the fear of violence does not necessarily lead to demobilisation or inaction when we locate their activism within a hierarchy of fears. By recognising that the fear of never knowing about their missing loved ones outweighs the fears of violence that they are exposed to on a day-to-day basis, we gain insight into why they choose ‘fight’, rather than ‘flight’.